Building failures: case studies in construction and design - McKaig, Thomas H. (New York, McGraw-Hill, 1962)
This collection of case studies has been assembled to help architects, engineers, and contractors build more safely. There is no intention to point a finger at anyone. Most building failures are accidents, and those who are involved in them are the victims of accidents, to whom sympathy and commiseration should be extended.
Includes index
II 16/01/2019
Loans
Keywords: Building failures